Analisis Laporan Realisasi Anggaran Pada Dinas Lingkungan Hidup Kota Samarinda - Sandy, Desy Ary; Deviyanti, Dwi Risma Deviyanti Risma; Diyanti, Ferry (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2020)
The purpose of the study was to determine the performance of spending from the 2014 budget realization report until 2016 in department of environment of Samarinda City. Data collection techniques used in this study were documentation an interviews. Documentation is carried out by collecting data on reports on the realization of the expenditure budget of the Samarinda City environment office and other reports as supporting research such as an overview of agencies, organizational structures, and others. Interviews were conducted to obtain information and confirmation of the contents of the report on the realization of the budget of the Samarinda City environment office. The analytical tool used in this study is the analytical of expenditure growth, expenditure compatibility ratio and expenditure efficiency ratio. Based on the analytical carried out in 2015 and 2016 the growth in expenditure of the department of environment of Samarinda City has decreased. This decreased in spending is in line with the reduction in the budget provided by the government to the Samarinda City Environmental Agency. The harmony analysis of direct expenditure on total expenditure has decreased in 2014 until 2016, while the analysis of indirect expenditure compatibility with total expenditure has increased from 2014 until 2016. The result of the analysis of expenditure efficiency show a percentage decline in 2015 and an increase in 2016.